Morphological studies of the cadaveric sclera after nonpenetrating sclerotomy by ND: YAG laser - A. E. Sineok; A. V. Zolotarev; G. A. Nikolaeva (Российский офтальмологический журнал, 2018)
Purpose: to reveal the changes of the morphological structure of cadaveric human sclera after Nd: YAG laser irradiation.Material and methods. Laser pulses (Nd: YAG) (Lumenis) (power 7.0–7.4 mW, pulse duration 4 ns, wavelength 1064 nm) were applied to the sclera of an isolated eyeball at a distance of 4 to 8 mm from the limbus. Three irradiation types were used: one series of single pulses, a series of triple pulses, and a series of six pulses.Results. Incisions created with single pulses showed insignificant surface defects of the sclera. In triple pulses, the defect of the anterior layers of the sclera capture affected 15 % of the scleral thickness, and in six pulses the defect reached 30 % of the scleral thickness.Conclusions. To achieve a punctate hole in the sclera, a single Nd: YAG pulse is insufficient. To obtain a significant depth of scleral incision at least a triple pulse is needed, which must be taken into account in clinical practice as well as in assessing the results of Nd: YAG laser impact on the rigidity of the sclera.